Pola Rembesan Air Tanah Gambut pada Model Seepage Tank yang Diberi Drainase Saluran Berpori - Ichwana Ichwana (Jurnal Agrista, 2009)
Peat Soil Water Intrusion Pattern in the Seepage Tank Model Was Given Drainase Porous ConduitsABSTRACT. Spread peat affected by tidal sea water have in some areas so as to overcome the pool or on the development of an area needs to be given some form of drainage holes in the side walls. The function of the hole in the wall of this channel will be capable of storing water through a hole in to the wall of the channel and dumped back at sea level began to recede. Drainage channel designed an open drainage channel porous trapezoidal shape. The pores are used to store the water into the soil through the hole so it can retain moisture in peat. The aim study is to determine the pattern of ground water seepage on peatland pore into the channel or leave the water seepage discharge channels and to know in order to support the reduction in peat puddles. Pores formed in the drainage channel can retain moisture and ground water due to peat during incoming tide in the channel partially soak into the ground through the pore channels with a trend toward the seepage pattern and left channels respectively y = -0.0061 x2 + 0.3066 x + 4.105 and y= 0.9579 e0,0925x water seepage discharge calculation using Darcy’s law into the soil when the water toward the channel to the first pair with length of time of 12 hours was 22.663. 10-3 cm3/det and discharge seepage which dihasilkan pada second pair with time to 24 hours of 42,019.10-3 cm3/det. Discharge water seepage into the soil when the water leaving the channel to the first pair at the time of 12 hours is 21,248.10-3 cm3/det and seepage generated at the second pair of 1,249.10-3 cm3/det.